Classic-Simulation Android Based Game of Fly and Learn in Elementary School Level - Diana, Diana; Darmawan, Dion (Bina Nusantara University, 2015)
The purpose of this research is to design classic simulation game application of Fly and Learn which is a mobile gaming application based on android smartphone that aims to provide children in elementary school level to learn with ease through a game. Fly and Learn is a classic simulation game which has a specific purpose to introduce the game of the plane where the children play as a pilot by a plane ride and also to train them in answering questions quickly and accurately on the way. The method used in this research is the waterfall model. The results achieved in the form of an application that can make a learning media for elementary school level students through the medium of game based on android. The conclusion of this research is that the created application successfully attracts students’ interest thus helping their learning process.